2010
DOI: 10.1016/j.semcdb.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Life and death of a BiP substrate

Abstract: BiP is the mammalian endoplasmic reticulum (ER) Hsp70 orthologue that plays a major role in all functions of this organelle including the seemingly opposing functions of aiding the maturation of unfolded nascent proteins and identifying and targeting chronically unfolded proteins for degradation. The recent identification of mammalian BiP co-factors combined with delineation of the ER degradation machinery and data suggesting that the ER is subdivided into unique regions helps explain how these different funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(187 citation statements)
references
References 76 publications
1
184
0
2
Order By: Relevance
“…In addition to the CNX/CRT complex, the other major chaperone system in the ER is the BiP/GRP78 or Hsp70 system (Hendershot 2004;Dudek et al 2009;Otero et al 2010). BiP (binding immunoglobulin protein) is one of the most abundant ER chaperones and serves multiple roles in the ER ranging from productive folding to ERAD.…”
Section: Folding By Chaperones and Co-chaperonesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the CNX/CRT complex, the other major chaperone system in the ER is the BiP/GRP78 or Hsp70 system (Hendershot 2004;Dudek et al 2009;Otero et al 2010). BiP (binding immunoglobulin protein) is one of the most abundant ER chaperones and serves multiple roles in the ER ranging from productive folding to ERAD.…”
Section: Folding By Chaperones and Co-chaperonesmentioning
confidence: 99%
“…The DnaJ family proteins, cochaperones of BiP, play a crucial role in regulating its various activities. Accumulated evidence suggests that ERdj3 and ERdj6 are primarily involved in productive-folding (ERAF), whereas ERdj4 and ERdj5 predominantly affect ERAD (Otero et al 2010). The process of transition from folding to degradation is far from clear.…”
Section: Recognition and Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to controlling the localization and activity of Hsp70s, J-domain proteins may also bind the substrate themselves and help with the initial delivery of the substrate to the Hsp70 chaperone. In the mammalian ER, there are seven J-domain proteins (ERdj1-7) that assist with the diverse functions of BiP in the ER (Otero et al 2010). ERdj1/Mtj1p and ERdj2/Sec63 are membrane-embedded and translocon-associated J-proteins.…”
Section: Classical Chaperonesmentioning
confidence: 99%
“…Our finding that overexpression of BiP suppressed the secretion of wild-type SIL1 argues that this is likely to be the normal mechanism of SIL1 retention. It is very possible that this mechanism extends to other soluble ER-resident proteins that do not have ER retention sequences, including many of the other ER-localized DnaJlike proteins (42). In keeping with this, studies to measure the concentration of BiP and resident ER-localized DnaJ-like proteins found that the concentration of BiP was significantly greater than the combined concentration of the ERdj proteins (43).…”
Section: Discussionmentioning
confidence: 93%